2007
DOI: 10.1063/1.2767265
|View full text |Cite
|
Sign up to set email alerts
|

On the properties of microsolvated molecules in the ground (S) and excited (S1) states: The anisole-ammonia 1:1 complex

Abstract: State-of-the-art spectroscopic and theoretical methods have been exploited in a joint effort to elucidate the subtle features of the structure and the energetics of the anisole-ammonia 1:1 complex, a prototype of microsolvation processes. Resonance enhanced multiphoton ionization and laser-induced fluorescence spectra are discussed and compared to high-level first-principles theoretical models, based on density functional, many body second order perturbation, and coupled cluster theories. In the most stable no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 34 publications
5
37
0
Order By: Relevance
“…electron circular dichroism, ECD) 1–3. However, proper assignment of spectra relies more and more on quantum mechanical (QM) computations for both interpretative and predictive aspects 4,5. Moving from the current practice of extracting numerical data from experiment to be compared with QM results toward the direct comparison between in vitro and in silico spectra would strongly reduce any arbitrariness and allow a proper account of the information hidden behind both position and shapes of spectral bands.…”
Section: Introductionmentioning
confidence: 99%
“…electron circular dichroism, ECD) 1–3. However, proper assignment of spectra relies more and more on quantum mechanical (QM) computations for both interpretative and predictive aspects 4,5. Moving from the current practice of extracting numerical data from experiment to be compared with QM results toward the direct comparison between in vitro and in silico spectra would strongly reduce any arbitrariness and allow a proper account of the information hidden behind both position and shapes of spectral bands.…”
Section: Introductionmentioning
confidence: 99%
“…(2,16,30−36) Isolated clusters can be readily prepared experimentally through use of jet-cooled supersonic expansions (molecular beams), (5,16,37−39) with electronic or infrared spectroscopy used to classify spectral changes of the chromophore upon cluster formation. The advent of velocity mapped ion imaging (VMI) has provided another tool for investigating the binding energies of clusters,(40−44) which the Anisole is a prototypical aromatic chromophore, (52) readily detected via R2PI methods, and relevant for studying different intermolecular interactions, as evident by the variety of reported studies on the formation and characterization of molecular complexes of anisole with simple systems including CO2, (33) NH3, (53) H2O, (31) and Ar. (54) In addition, the anisole dimer has been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…The subtle competition between the different possible interactions are the subject of recent spectroscopic studies in supersonic jets. [255][256][257][258][259] For anisole·water 256,257 and anisole·methanol 259 it has been found that complexes with an OH· · · O hydrogen bond are more abundant than structures dominated by purely dispersive or OH· · · π interactions. In contrast to these findings, the experimental rotational constants of anisole·NH 3 measured with high resolution LIF spectroscopy (laser induced fluorescence) fit best for a structure in which ammonia forms an NH· · · π hydrogen bond to the anisole moiety.…”
Section: Complexes With Anisolementioning
confidence: 99%
“…In contrast to these findings, the experimental rotational constants of anisole·NH 3 measured with high resolution LIF spectroscopy (laser induced fluorescence) fit best for a structure in which ammonia forms an NH· · · π hydrogen bond to the anisole moiety. 258 (Anisole) 2 is a π-stacked centrosymmetric (C i ) dimer. 261 Due to symmetry restrictions, the S 1 (A g ) state cannot be excited by one-photon excitation, the lowest state that can be optically excited is the…”
Section: Complexes With Anisolementioning
confidence: 99%